Generøsitetens teologi - Gregersen, Niels Henrik (Dansk Teologisk Tidsskrift, 2008)
„A Theology of Generosity“, aims to reinterpret the doctrine of grace in the light of postmodern discussions on gift and giving. It is argued that the idea of a divine-human reciprocity is already entailed in the Old Testament term berakah (blessing/thanking) as well as in the New Testament concepts of eulogéo (blessing/praising) and cháris (grace). The concept of reciprocity, however, is in need of a phenomenological clarification. Three conditions for a suitable concept of divine generosity and giving are identified: (1) God must be able to carry the risk of being the first donor without receiving returns; the almighty God is not in need of returns. (2) Grace should not be seen as mere object; rather the self-giving God is present in the gift of grace. (3) The God-human relation should not be conceived of as merely a bilateral relation (with immediate or postponed counter-gifts); rather the grace of God facilitates a wider circulation of gifts. With the gift of grace, human beings receive an impulse to pass on the gifts of grace to other creatures within a multilateral network of giving and receiving. Never, however, should the human ability to do so be seen as a condition for divine generosity.